Descending perineum syndrome in children: Pathophysiology and diagnosis - M. D. Levin (Вестник рентгенологии и радиологии)
Objective: to propose a safer, simpler, and more exact method for the diagnosis of descending perineum syndrome (DPS).Material and methods. A total of 194 patients aged 5 days to 15 years were examined and divided into 2 groups: Group 1 consisted of 65 patients without anorectal anomalies (AA); Group 2 comprised 129 patients, including 66 children with functional constipation,55 with AA and visible fistulas, who were preoperatively examined, and 8 patients with anorectal angle (ARA), who were postoperatively examined. All the patients underwentirrigoscopy that was different from standard examination in the presence of X-ray CT contrast marker near the anus. Results and conclusion. DPS is caused by puborectalis muscle dysfunction. A method was proposed to evaluate the status of the puborectalis muscle from the distance between the position of the ARA and the marker near the anus. This not only promotesan exacter estimate of DPS, but also allows refusal of defecography. The use of a barium enema with the minimum number of X-ray films decreases dose of ionizing radiation hazard and permits the use of this procedure not only in adults, but also in children with chronic constipation, fecal incontinence, and in AA for both pre- and postoperatively assessment of the causes of complications.